2016
DOI: 10.5511/plantbiotechnology.16.1006a
|View full text |Cite
|
Sign up to set email alerts
|

A comparative <i>in vitro</i> study of salt tolerance in cultivated tomato and related wild species

Abstract: Salinity stress is a major abiotic stress for plants worldwide. This study was carried out to determine the variation in salt tolerance for 12 different genotypes belonging to three different tomato species: Solanum lycopersicum (L), S. peruvianum (L) and S. pimpinellifolium (L). Shoot apices and callus cultures were exposed to different levels of salinity stress ranging from no salt (control) to 100, 200 and 300 mmol L −1 NaCl. All growth and physiological parameters were significantly affected by salt stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
4
37
1
1
Order By: Relevance
“…Many different traits contribute to salinity tolerance, which are species- and developmental stage-dependent (Munns, 2002; Jones et al , 2015). In glycophytes, salt tolerance also involves the accumulation of compatible solutes, such as proline, in the cytosol and organelles for osmotic adjustment and osmoprotection (Yokoi et al , 2002; Zaki and Yokoi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many different traits contribute to salinity tolerance, which are species- and developmental stage-dependent (Munns, 2002; Jones et al , 2015). In glycophytes, salt tolerance also involves the accumulation of compatible solutes, such as proline, in the cytosol and organelles for osmotic adjustment and osmoprotection (Yokoi et al , 2002; Zaki and Yokoi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most experimental work on salinity tolerance has focused on shoot Na + exclusion ( Møller et al , 2009 ; Huang et al , 2013 ; Niu et al , 2018 ). However, there is increasing evidence that this is not the sole mechanism for salinity tolerance ( Rajendran et al , 2009 ; Munns et al , 2016 ; Zaki and Yokoi, 2016 ). Some species or genotypes can maintain a relatively high Na + concentration in their shoots without major negative impacts on growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy, termed a tissue-tolerance mechanism ( Munns et al , 2016 ), is observed in both halophytes ( Wang et al , 2007 ; Adolf et al , 2013 ) and glycophytes (e.g. Triticum aestivum , Genc et al , 2007 ; T. monococcum , Rajendran et al , 2009 ; lettuce, Bartha et al , 2015 ; tomato, Gálvez et al , 2012 ; Zaki and Yokoi, 2016 ; rice, Prusty et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to cope with enriched salt conditions, plants implement a plethora of morphological, physiological and biochemical adaptations, with the effect of developmental stage and salt levels being critical in the efficiency of the activated defense mechanism to mitigate stress injury [26]. The adaptability of seedlings under salt stress may also reflect higher salt tolerance at advanced growth stages [27].…”
Section: Discussionmentioning
confidence: 99%